Disagreement and Optimal Security Design - Juan M. Ortner; Martin C. Schmalz (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study optimal security design when the issuer and market participants agree to disagree about the characteristics of the asset to be securitized. We show that pooling assets can be optimal because it mitigates the effects of disagreement between issuer and investors, whereas tranching a cash-flow stream allows the issuer to exploit disagreement between investors. Interestingly, pooling and tranching can be complements. The optimality of debt with or without call provisions can be derived as a special case. In a model with multiple financing rounds, convertible securities naturally emerge to finance highly skewed ventures.
Keywords: G30; G32; D84; D86; 330; disagreement; security design; optimism; overconfidence; pooling; behavioral finance